AN ANALYSIS OF CODE SWITCHING IN FACEBOOK: A DISCOURSE APPROACH - Syam Tenrisanna Andi; Furwana Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
This study aimed at identifying the type of code switching used in the facebook and finding out the reasons why the people switched their language. The respondents of this study were Indonesianfacebook users. The data were taken from 10 facebookusers' profiles comment and status columns. The writer found that the facebookers used three types of code switching namely: tag switching, inter-sentential switching and intra-sentential switching. The facebookers switched their language for: (1) the activation of the speakers speech repertoire, (2) style markers, (3) switch the code, (4) switch for emphasis, (5) switch to indicate topic, (6) switch to separate feelings from facts, (7) switch to frame discourse, and (8) switch to intent on clarifying the speech content for the interlocutor